Framework for automatic singing transcription: Database and Software. - Molina, Emilio; Barbancho-Pérez, Ana María; Tardón-García, Lorenzo José; Barbancho-Pérez, Isabel (Universidad de Málaga, 2023)
This Research data consists of a cross-annotated dataset of 1154seconds and a novel set of evaluation measures, able to report thetype of errors made by the system. Both the dataset, and a Matlabtoolbox including the presented evaluation measures, are freely available. In order to show the utility of the work presented in thispaper, we have performed an detailed comparative study of threestate-of-the-art singing transcribers plus a baseline method, lead-ing to relevant information about the performance of each method.
Keywords: Música - Proceso de datos; Automatic singing transcription; Singing Data Base; Annotated dataset; Evaluation measures; Evaluation framework